Assessment for the organizational model of the research system of social sciences in Vietnam - Dinh, Tran Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
Social sciences in Vietnam have a long years history and they keep a very important position among the system of sciences. The organizational model of the research system of social sciences now passes a change process oriented to modernity, democracy, socialization and autonomy. This change would link closely scientific research activities and graduate and post-graduate teaching activities. This paper presents studies, analyses and assessments of the strong aspects as well as shortcomings of the organizational model of the research system of social-human sciences in Vietnam during the recent time. On basis of outcomes of studies, many recommendations are proposed for renovation of the organizational model of the research system of social-human sciences in Vietnam in the coming time. Code: 11040801